Environmental online communication - Scharl, Arno, 1970- (Advanced information and knowledge processing,, 2004)
"The Internet and wireless communication networks are transforming the way society handles the explosive growth and the dwindling half-life of environmentally relevant information. How can we leverage new technologies to advocate sustainability and the protection of natural ecosystems? This book presents an interdisciplinary investigation of this question, combining theoretical foundations of environmental online communication with pioneering conceptual work and case studies of successful information systems."--BOOK JACKET.